THE EFFECT OF WORK MOTIVATION, WORK DISCIPLINE AND COMPENSATION ON EMPLOYEE PERFORMANCE AT PT TELEKOMUNIKASI INDONESIA (TELKOM) SURABAYA - Febri Ali Wijaya, Histwo; Ida Ayu Nuh Kartini (SEAN Institute, 2022)
This study aims to analyze the effect of work motivation, work discipline and compensation on employee performance at PT. Telekomunikasi Indonesia (Telkom) Surabaya), Jl. Dr. Ir. H. Soekarno No. 175, Klampis Ngasem, Kec. Sukolilo, City of SBY, East Java 60116. This study uses data sampling from 50 employees through the distribution of questionnaires. The type of data used is quantitative. In this study, the t-test showed that the work motivation variable had a partial influence on employee performance with a regression coefficient value of Work Motivation (X1) of 4.2774 and the value of the Work Discipline regression coefficient (X2) of 3.793 while Compensation (X3) had a coefficient value of regression of 2,645. F test obtained f count > f table that is 124.175 > 2.81 so it can be concluded that the independent variables Work Motivation (X1), Work Discipline (X2), and Compensation (X3) have a significant effect simultaneously on the dependent variable Employee Performance (Y ). This research is expected to be able to support the basic decision making for PT. Telekomunikasi Indonesia (Telkom) Surabaya). related to Work Motivation (X1), Work Discipline (X2), Compensation (X3). In addition, this research is expected to be able to provide new knowledge about Work Motivation (X1), Work Discipline (X2), Compensation (X3) at PT. Telekomunikasi Indonesia (Telkom) Surabaya.